2003
DOI: 10.4049/jimmunol.170.6.3002
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Signal Enhances Apoptosis of CD8 T Cells After Strong TCR Ligation

Abstract: High avidity ligation of the TCR induces negative selection in the thymus and can also induce apoptosis of peripheral T cells. Costimulation through CD28 enhances T cell activation and facilitates negative selection in the thymus, but the role of CD28 in peripheral T cell deletional tolerance has not been investigated. We used 2C CD28 wild-type and 2C CD28-deficient strains to assess the effects of CD28 and TCR avidity on peripheral T cell expansion and apoptosis. We compared the activation, division, expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…There have been reports of CD28 having both pro-apoptotic 46,47 and anti-apoptotic effects. [48][49][50] Studies on the aging immune system have found that the number of CD8 þ CD28 À T cells increases with age and that these cells are resistant to apoptosis, having increased bcl-2 expression and decreased caspase 3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of CD28 having both pro-apoptotic 46,47 and anti-apoptotic effects. [48][49][50] Studies on the aging immune system have found that the number of CD8 þ CD28 À T cells increases with age and that these cells are resistant to apoptosis, having increased bcl-2 expression and decreased caspase 3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that costimulation and highavidity ligation of the TCR can play a major role in the negative selection of T cells in the thymus and the periphery (13)(14)(15). By the use of altered peptide ligands (APLs) 3 with different binding affinity to the TCR, it has been shown in CD4 ϩ T cells that differences in TCR activation lead to uncoupling of cytokine production and cell proliferation.…”
mentioning
confidence: 99%
“…The role of high concentrations of Ag has been investigated using in vitro models and the reports showed a suppression of the proliferative response, which was the consequence of the induction of anergy (3) or apoptosis (4) mediated by CD95/CD178 interaction (5) of CD4 ϩ T cell, whereas in CD8 ϩ effector CTL, apoptosis was mediated by TNFRII/TNF interaction (6,7). In models using TCR transgenic mice, supraoptimal peptide-MHC stimulation in vivo induced CD4 ϩ or CD8 ϩ T cell deletion by apoptosis (4,8,9). In most of these models, deletion of specific T cells occurs after an initial phase of expansion and is thought to result from re-exposure of cycling T lymphocytes to Ag.…”
mentioning
confidence: 99%